Rewiring the Mind: How Faith and Biology Interact in Personal Transformation - Insights from Bruce Lipton’s Biology of Belief - Siti Khadijah Binte Mahfuh; Dodi S. Truna (Tabayyun : Journal Of Islamic Studies, 2025)
This study explores the intricate relationship between Islamic faith and biological processes in shaping personal transformation. Drawing upon both spiritual principles and modern neuroscience, it investigates how core Islamic practices—such as Sabr (patience), Tawakkul (trust in Allah), and Dhikr (remembrance of Allah)—influence cognitive and emotional well-being. In parallel, the research incorporates insights from Bruce Lipton's "The Biology of Belief," which posits that beliefs and perceptions can directly affect cellular function and biological processes. The study employs a mixed-methods approach, blending qualitative and quantitative data to examine how both Islamic spiritual practices and Lipton's theory of belief-driven biology contribute to "rewiring" the mind and body. This research aims to bridge the gap between spiritual faith and modern science, demonstrating that Islamic beliefs, along with a scientific understanding of the mind-body connection, can foster profound personal transformation, enhance mental health, and promote overall well-being. By integrating faith-based practices with scientific insights, the study offers a holistic approach to emotional stability and cognitive resilience.